A Complete Lattice Lossless Compression Storage Model - Zhi Huilai (Institute of Advanced Engineering and Science, 2014)
In this paper, a complete lattice lossless compression storage model is proposed to improve the storage efficiency. In order to build the proposed model, first all the upper and lower irreducible elements of the complete lattice are identified respectively, then an isomorphic mapping form the complete lattice to a concept lattice is founded, and finally a matrix is used to store the formal context of the concept lattice. Compared with using adjacent matrix, example and analysis show that the proposed method can improve the storage efficiency of complete lattice. DOI: http://dx.doi.org/10.11591/telkomnika.v12i8.5854